Mathematical modelling and stability analysis for grid-connected cascaded H-bridge converter - Bai, Xiaoyi (2018)
When power converters are employed to connect the renewable power resources to the grid, the grid inductance can typically be quite significant because wind farms and solar power stations are located far away from the converters. The non-negligible grid inductance interacts with the Phase Locked Loop (PLL) which is assisting the grid side current controller with the phase angle of grid voltage and furthermore interacts with the DC-link voltage controller. It is known that the inductance of the grid side transmission line would distort the input voltage of PLL at the point of common coupling and this interference can even lead to the instability of the converter operation. However, the accurate prediction of the stability thresholds of the PLL configuration related to the grid inductance was missing which requires advanced modelling techniques.